Răspuns :
a-b=c
a+b+c=10200
(a+b+c)-(a-b+c)=a+b+2c
10200=4c
c=10200:4
c=2550
a-b=2550
(a+b)+c=10200
a+b=10200-c
a+b=10200-2550
a+b=7650
a=(a+b)-c
a=7650-2550
a=5100
a-c=b
b=5100-2550
b=2550
a-b=c
5100-2550=2550
a+b+c=10200
5100+2550+2550=10200
R=>a=5100
b=2550
c=2550
a+b+c=10200
(a+b+c)-(a-b+c)=a+b+2c
10200=4c
c=10200:4
c=2550
a-b=2550
(a+b)+c=10200
a+b=10200-c
a+b=10200-2550
a+b=7650
a=(a+b)-c
a=7650-2550
a=5100
a-c=b
b=5100-2550
b=2550
a-b=c
5100-2550=2550
a+b+c=10200
5100+2550+2550=10200
R=>a=5100
b=2550
c=2550